Can internal strategic alignment influence performance? An empirical research applying structural equation modelling. Issue 3 (6th August 2018) - Prieto, Vanderli Correia; de Carvalho, Marly M.
Abstract : Purpose: The purpose of this paper is to investigate the impact of internal strategic alignment (ISA) on business performance. A model is developed in which internal alignment is explained by the covariance between vertical and horizontal alignment. The perspective of business strategy implementation is adopted in order to support the theoretical relationship between the variables. Design/methodology/approach: The partial least squares method, a structural equation modeling technique, is applied to estimate the model. Findings: The results provide empirical validation for the model and confirm the positive relationship between internal alignment and business performance. Practical implications: The ISA model is an essential aid for executives when implementing strategies and the validated research instrument can be applied for firms as a diagnosis of internal alignment in the organization. Originality/value: The research contributed to meet the need for studies involving strategy implementation, as its formulation has already been emphasized, as well as to the need for models of strategic internal alignment that include activities relevant to the successful execution of the strategy, and to the need for alignment studies based on a holistic perspective. Abstract : Objetivo: O estudo foi conduzido com o objetivo de avaliar o impacto do alinhamento estratégico interno sobre o desempenho do negócio. Foi desenvolvido um modelo em que o alinhamento interno é explicado pela covariância entre o alinhamento vertical e o alinhamento horizontal. É adotada a perspectiva da implementação da estratégia de negócios para apoiar a relação teórica entre as variáveis. Diseño/metodología/enfoque: Os dados foram processados e validados por meio da técnica de Modelagem de Equações Estruturais com estimação pelo método Partial Least Squares (PLS). Resultados: Os resultados dão validação ao modelo e confirmam a relação positiva entre o alinhamento estratégico interno e o desempenho organizacional. Implicações práticas: O Modelo de Alinhamento Estratégico Interno define um conjunto de ações que podem servir de guia para os executivos quando da implementação da estratégia. Os instrumentos validados podem ser aplicados pelas organizações para realizar um diagnóstico do alinhamento interno. Originalidad/valor: Esta pesquisa traz contribuições quanto à necessidade de estudos envolvendo a implementação da estratégia, uma vez que ênfase tem sido dada à formulação; quanto à escassez de modelos de alinhamento estratégico interno que integrem atividades relevantes para a execução bem sucedida da estratégia e à necessidade de estudos de alinhamento empregando a perspectiva holística.